2017
DOI: 10.1021/acs.jpclett.7b02590
|View full text |Cite
|
Sign up to set email alerts
|

Direct Writing and Aligning of Small-Molecule Organic Semiconductor Crystals via “Dragging Mode” Electrohydrodynamic Jet Printing for Flexible Organic Field-Effect Transistor Arrays

Abstract: Patterning and aligning of organic small-molecule semiconductor crystals over large areas is an important issue for their commercialization and practical device applications. This Letter reports "dragging mode" electrohydrodynamic jet printing that can simultaneously achieve direct writing and aligning of 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS-PEN) crystals. Dragging mode provides favorable conditions for crystal growth with efficient controls over supply voltages and nozzle-to-substrate distances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 52 publications
2
61
2
Order By: Relevance
“…However, up to now, almost all the reported optimizations of the solution‐processed OTFTs have been performed on rigid substrates, where many optimization conditions, for example, self‐assembled monolayer treatment, and high‐temperature or solvent vapor annealing, are hardly available for flexible polymer dielectric materials and substrates owing to the randomly oriented polymer chains, or poor resistance to high temperature and organic solvents. A few research groups have observed the performance degradation when the fabrication of OTFTs was replaced from the rigid substrate to the flexible substrate . Therefore, it is more desirable to optimize the mobility directly based on ultrathin flexible organic devices via solution‐processed techniques.…”
mentioning
confidence: 99%
“…However, up to now, almost all the reported optimizations of the solution‐processed OTFTs have been performed on rigid substrates, where many optimization conditions, for example, self‐assembled monolayer treatment, and high‐temperature or solvent vapor annealing, are hardly available for flexible polymer dielectric materials and substrates owing to the randomly oriented polymer chains, or poor resistance to high temperature and organic solvents. A few research groups have observed the performance degradation when the fabrication of OTFTs was replaced from the rigid substrate to the flexible substrate . Therefore, it is more desirable to optimize the mobility directly based on ultrathin flexible organic devices via solution‐processed techniques.…”
mentioning
confidence: 99%
“…This suggests that the TIPS‐pentacene molecules pack in an edge‐on orientation on the FAGPTi/PET film. [ 39 ] This edge‐on orientation is positively correlated with lateral charge transport because the intermolecular π–π stacking is aligned in a direction parallel to the substrate. [ 39 ] Regardless of the bending stress, their orientations and crystallinities were well‐maintained.…”
Section: Resultsmentioning
confidence: 99%
“…To continuously draw TIPS‐pentacene crystals along the nozzle, EHD printing was performed in the dragging mode. [ 39 ] A V S of 5 V was applied between a stainless‐steel nozzle and a ground substrate with a height of 20 µm. The substrate temperature was maintained at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…As summarized in Table 1, compared to the (001) peak for the pristine P-29-DPPDTSE sample, that for the annealed sample showed a lower FWHM value, yielding a greater coherence length of 400.7 Å. This result was indicative of a smaller grain boundary of the annealed P-29-DPPDTSE sample, which could reduce the barrier for changes to efficient transport [23,24].…”
Section: Resultsmentioning
confidence: 99%